"Initium ut esset, creatus est homo": Iris Murdoch on Authority and Creativity - Altorf, Marije (Text Matters: A Journal of Literature, Theory and Culture, 2011)
In 1970 the British novelist and philosopher Iris Murdoch published both her thirteenth novel, A Fairly Honourable Defeat, and her best known work of philosophy, The Sovereignty of Good. Given the proximity of these publication dates, it does not surprise that there are many points of comparison between these two works. The novel features, for instance, a character writing a work of moral philosophy not unlike Murdoch's own The Sovereignty of Good, while another character exemplifies her moral philosophy in his life. This article proposes a reading of the novel as a critical commentary on the philosophical work, focusing on the tension between creation and authority. While Murdoch considers humans to be first and foremost creative, she is at the same time wary of the misleading nature of any act of creation. For Murdoch, any creator and any creation—a beautiful picture as well as a watertight theory—may transmit a certain authority, and that authority may get in the way of acknowledging reality. It thus hinders the moral life, which for Murdoch should be thought of as a life of attention—to reality and ultimately to the Good—rather than a series of wilful creations and actions. A Fairly Honourable Defeat queries the possibility and danger of creation, through different characters as well as through images of cleanliness and messiness. Thus, the character whose book of moral philosophy is challenged and who is found wanting when putting his ideas to practice, likes ‘to get things clear’ (176). Another character, whose interferences create the novel's drama, has a self-confessed ‘passion for cleanliness and order’ (426). The saint of the story, in contrast, does not interfere unless by necessity, and resides in one of the filthiest kitchens in the history of literature. Yet, none of the main characters exemplifies a solution to the tension between creation and authority found in Murdoch's philosophy. An indication of a solution is found in a minor character, and in his creations of outrageous bunches of flowers, unusual meals, and absurd interiors. Yet, its location in a subplot suggests that this solution is not in any way final. It is concluded that any final solution should not be expected, not in the least because of the pervasive nature of the tension between creation and authority, which goes well beyond Murdoch's own authorship.